Status Evolution and Competition: Theory and Evidence - Washington, Marvin; Zajac, Edward J. (Academy of Management Journal, 2005)
In this study, we (1) clarify and distinguish the concept of status, (2) identify and analyze the institutional and organizational factors that can lead to differences in organizational status over time, and (3) empirically assess the privileges implied by such differences. Using extensive longitudinal data on competitive intercollegiate athletics, we found that status was a significant predictor of whether a college was invited to participate in the NCAA postseason basketball tournament, independently of performance considerations.